The 'omics' revolution: redefining the understanding and treatment of allergic skin diseases. Issue 5 (October 2016) - Oliva, Margeaux; Renert-Yuval, Yael; Guttman-Yassky, Emma
Abstract : Purpose of review: To evaluate how the genomic, transcriptomic, and proteomic profiles of allergic skin diseases, like atopic dermatitis and allergic contact dermatitis, contribute to their understanding and promote their therapeutic development. Recent findings: The '-omics' revolution has facilitated the quantification of inflammatory skin diseases at the molecular level, expanding our understanding of disease pathogenesis. It has also greatly expanded once-limited treatment options and improved the ability to define posttreatment improvements, beyond clinical scores. The findings on the genomic/transcriptomic level are also complemented by proteomic data, contributing to the understanding of the later changes taking place in the final stages of protein formation. Atopic dermatitis is defined as a Th2/Th22 polarized disease with some contributions of Th17 and Th1 pathways. In atopic dermatitis, studies of biologics and small molecules, targeting specific pathways upregulated in atopic dermatitis, seem to provide well tolerated alternatives to conventional immunosuppressive therapies (i.e. corticosteroids and cyclosporine A), particularly for severe patients. Allergic contact dermatitis is defined as having Th1/Th17-centered inflammation, especially with nickel-induced disease, but additional pathways, including Th2 and Th22, are upregulated with other allergens (i.e. fragrance). Summary: Supplementing studies of allergic skin diseases with '-omics' approaches are transforming the pathogenic understanding, diagnosis and, perhaps, also the treatment of these diseases.